2014
DOI: 10.5296/jas.v2i2.6046
|View full text |Cite
|
Sign up to set email alerts
|

Economic Efficiency of Smallholder Dairy Farmers in Swaziland: An Application of the Profit Function

Abstract: The purpose of the study was to analyse the economic efficiency of smallholder dairy farmers in Swaziland. Specifically, the study sought to describe the socio-economic characteristics of dairy farmers in Swaziland. The smallholder farmers are classified into: smallholder farmers, medium-scale farmers, and large-scale dairy farmers. The specific objectives of the study were to: estimate the economic efficiency of smallholder dairy farmers in Swaziland; identify factors affecting the economic efficiency of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…The results of Herrero et al (2010) and Masuku et al (2014), also revealed that one of the factors that significantly affected economic efficiency of dairy farmers was herd size or the number of dairy cattle ownership with a positive impact. Related to business profit, Sari et al (2013) stated that the dairy farm was not profitable.…”
Section: Characteristics and Business Performance Of Dairy Farm Of Mpmentioning
confidence: 63%
“…The results of Herrero et al (2010) and Masuku et al (2014), also revealed that one of the factors that significantly affected economic efficiency of dairy farmers was herd size or the number of dairy cattle ownership with a positive impact. Related to business profit, Sari et al (2013) stated that the dairy farm was not profitable.…”
Section: Characteristics and Business Performance Of Dairy Farm Of Mpmentioning
confidence: 63%
“…It has been used to analyze economic efficiency by Masuku et al (2014) and Sajjad and Khan (2010). According to Kopp and Smith (1980), Cobb-Douglas…”
Section: Stochastic Frontier Production and Cost Functionmentioning
confidence: 99%
“…Integrating vegetable production in a farming system has contributed substantially to food and nutrition security as the vegetables complement stable foods for a balanced diet by providing vitamins and minerals (Gani and Adeoti 2011;Afari-sefa and Dinssa, 2015). Improving farmers' participation in markets is a vital determinant of prosperity and advancement (Getachew and Bamlak, 2014;Masuku et al, 2014). In many rural areas, vegetable market participation plays a crucial role in generating better income and enhancing the welfare of smallholder farmers and thus contributes to their livelihoods.…”
Section: Introductionmentioning
confidence: 99%